Dataset on structure, stability and myocardial effects of a new hybrid aspirin containing nitrogen monoxide-releasing molsidomine moiety - Kitti Szőke; Attila Czompa; István Lekli; Péter Szabados-Fürjesi; Mihály Herczeg; Magdolna Csávás; Anikó Borbás; Pál Herczegh; Árpád Tósaki (Data in Brief, 2019)
Herein 1H and 13C NMR spectra of ERJ-500, a new hybrid aspirin derivative, covalently conjugated to nitrogen monoxide donor linsidomine are presented as well as NMR spectra of its synthetic intermediate compounds. HPLC-MS measurements data are also included, demonstrating the stability of the linsidomine-aspirin hybrid in oxidation reactions. This data article also concerns miscellaneous myocardial parameters of isolated rat hearts as a complementation of the tables shown in the paper entitled “A new, vasoactive hybrid aspirin containing nitrogen monoxide-releasing molsidomine moiety” Szoke et al., 2019. Column tables represent data of aorta flow, aortic pressure, derivated aortic pressure and cardiac output. Keywords: ERJ-500, Hybrid aspirin, Molsidomine